Pengaruh Suhu Cetakan Terhadap Produk Plastik Berbahan Polyprophylen (PP) Pada Injection Molding - F, Fadhlurrohman; Umurani, Khairul; A, Affandi; Nurdin, Hendri; Nasution, Arya Rudi (Rekayasa Material, Manufaktur dan Energi, 2022)
The manufacture of plastic products is carried out using the Plastic Injection Molding (PIM) method. The Injection Molding method is the process of forming a workpiece from granular compound material which is placed into a hopper and enters the injection cylinder which is then pushed through the nozzle. The materials used in this research are as follows: Polypropylene (PP) Plastic Seeds and the selected temperatures are 160C, 170C, 180C, 190C, 200C. After conducting several experiments on temperature variations of moving and stationary molds, it is known that the mold must have the right temperature to produce the product. This can be seen from the results of the research that the right mold temperature is 71C at rest and the heating temperature for moving molds is 63C the result is that the product has dried.